Failure of the PTEN/aPKC/Lgl Axis Primes Formation of Adult Brain Tumours in Drosophila. (27th December 2017) - Paglia, Simona; Sollazzo, Manuela; Di Giacomo, Simone; de Biase, Dario; Pession, Annalisa; Grifoni, Daniela
Abstract : Different regions in the mammalian adult brain contain immature precursors, reinforcing the concept that brain cancers, such as glioblastoma multiforme (GBM), may originate from cells endowed with stem-like properties. Alterations of the tumour suppressor gene PTEN are very common in primary GBMs. Very recently, PTEN loss was shown to undermine a specific molecular axis, whose failure is associated with the maintenance of the GBM stem cells in mammals. This axis is composed of PTEN, aPKC, and the polarity determinant Lethal giant larvae (Lgl): PTEN loss promotes aPKC activation through the PI3K pathway, which in turn leads to Lgl inhibition, ultimately preventing stem cell differentiation. To find the neural precursors responding to perturbations of this molecular axis, we targeted different neurogenic regions of the Drosophila brain. Here we show that PTEN mutation impacts aPKC and Lgl protein levels also in Drosophila . Moreover, we demonstrate that PI3K activation is not sufficient to trigger tumourigenesis, while aPKC promotes hyperplastic growth of the neuroepithelium and a noticeable expansion of the type II neuroblasts. Finally, we show that these neuroblasts form invasive tumours that persist and keep growing in the adult, leading the affected animals to untimely death, thus displaying frankly malignant behaviours.